EFQM model implementation in a Portuguese Higher Education Institution - Santos, Ricardo (2019)
Education sector, and particularly, Higher Education Institutions (HEI), is nowadays an increasingly competitive sector, where the HEI’s success, relies on stakeholder’s recognition, along with their capacity to attract funding, to achieve sustainability. To attends such demands, HEI tends to incorporate into their strategy, Internal Quality Assurance Systems (IQAS). Additionally, and according to some works, existed on literature, HEI should follows a logic of continuous improvement, through the services provided to their stakeholders, where EFQM (European Foundation for Quality Management) model, arises as an alternative solution to be considered. However, and although the success achieved with this model on private sector, there are no certainties about the results of their implementation in HEI, since some of the adopted models have a set of techniques based on theories, sometimes incompatible within HEI nature. Therefore, and by using the case study methodology, it is intended to analyze the feasibility of an IQAS implementation, based on the EFQM model, in an Engineering School in Portugal. For this purpose, they are identified some advantages and difficulties found within its implementation, as well as ways to overcome them, contributing therefore with some answers for a better EFQM implementation into a HEI in general.